Serangan Arab Saudi Ke Atas Houthi (2011-2015): Kesannya ke atas Yaman: Saudi Arabia Attacks on Houthi (2011-2015): Impact on Yemen - Hussin, Muhammad Khairul Iman; Mohd Nor, Mohd Roslan (Journal Al-Muqaddimah, 2023)
Saudi Arabia’s attack in 2015 is the biggest threat to the stability of Yemen. The Saudi attacks were launched relentlessly, especially on the Houthi group, which was considered to be militants following the rise of the group involved, which led to the coup of the Yemeni government during Uprising 2011. Many regions under the influence of the Houthis were attacked and even all forms of assets belonging to the Houthi army were also destroyed. But despite the attack, millions of Yemenis became victims. Thus, this study aims to analyze the impact on Yemen by using a thematic analysis method through research on three main scopes collectively; first, from a political point of view, second from a social point of view and third from an economic point of view. The results of the study found that the effects of the conflict led to political instability, recession and social backwardness.